Comparative isotope ecology of African great apes. Issue 101 (December 2016) - Oelze, Vicky M.; Fahy, Geraldine; Hohmann, Gottfried; Robbins, Martha M.; Leinert, Vera; Lee, Kevin; Eshuis, Henk; Seiler, Nicole; Wessling, Erin G.; Head, Josephine; Boesch, Christophe; Kühl, Hjalmar S.
Abstract: The isotope ecology of great apes is a useful reference for palaeodietary reconstructions in fossil hominins. As extant apes live in C3 -dominated habitats, variation in isotope signatures is assumed to be low compared to hominoids exploiting C4 -plant resources. However, isotopic differences between sites and between and within individuals are poorly understood due to the lack of vegetation baseline data. In this comparative study, we included all species of free-ranging African great apes ( Pan troglodytes, Pan paniscus, Gorilla sp. ). First, we explore differences in isotope baselines across different habitats and whether isotopic signatures in apes can be related to feeding niches (faunivory and folivory). Secondly, we illustrate how stable isotopic variations within African ape populations compare to other extant and extinct primates and discuss possible implications for dietary flexibility. Using 701 carbon and nitrogen isotope data points resulting from 148 sectioned hair samples and an additional collection of 189 fruit samples, we compare six different great ape sites. We investigate the relationship between vegetation baselines and climatic variables, and subsequently correct great ape isotope data to a standardized plant baseline from the respective sites. We obtained temporal isotopic profiles of individual animals by sectioning hair along its growth trajectory. Isotopic signatures of great apes differed between sites, mainly as vegetation isotope baselines were correlated with site-specific climatic conditions. We show that controlling for plant isotopic characteristics at a given site is essential for faunal data interpretation. While accounting for plant baseline effects, we found distinct isotopic profiles for each great ape population. Based on evidence from habituated groups and sympatric great ape species, these differences could possibly be related to faunivory and folivory. Dietary flexibility in apes varied, but temporal variation was overall lower than in fossil hominins and extant baboons, shifting from C3 to C4 -resources, providing new perspectives on comparisons between extinct and extant primates.